On the Location of Zeros of a Polynomial (Analysis in Theory and Applications, 2012)
In this paper we extend Enestrom-Kakeya theorem to a large class of polynomials with complex coefficients by putting less restrictions on the coefficients. Our results generalise and extend many known results in this direction.